Knowledge Of Princess Adoles About Personal Hygiene When Does The Princess Junior High School Students Know - Ida Susila; Armenia Kastar (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Self-care for adolescents during vaginal discharge needs to be taught so that young women can avoid infectious diseases due to poor hygiene during vaginal discharge. The purpose of this study was to determine the personal hygiene knowledge of young women with vaginal discharge cases. Researchers used 50 respondents and all met the inclusion criteria. Sampling using total sampling. All variables were measured using a closed questionnaire and analyzed using descriptive analysis. The results of the research were that the age characteristics of the respondents were mostly 13 years old. The results of research on personal hygiene knowledge, most of the young women had poor knowledge of 23 respondents (46%) about personal hygiene. For cases of vaginal discharge experienced, most of the vaginal discharge experienced was abnormal vaginal discharge, namely 27 respondents (54%). Knowledge is not good due to limited access to information and facilitators at the educational institution.